Bullous pemphigoid: The role of type 2 inflammation in its pathogenesis and the prospect of targeted therapy - Zhang, Luyao; Chen, Zihua; Wang, Lanting; Luo, Xiaoqun (Frontiers in Immunology, 2023)
Bullous pemphigoid is an autoimmune disease that mainly occurs in the elderly and severely affects their health and life. Traditional therapy for bullous pemphigoid is mainly based on systematic use of corticosteroids, but long-term use of corticosteroids will bring a series of side effects. Type 2 inflammation is an immune response mainly mediated by group 2 innate lymphoid cells, type 2 T helper cells, eosinophils and inflammatory cytokines such as IL-4, IL-5 and IL-13. Recently, studies have shown that in patients with bullous pemphigoid, immunoglobulin E and eosinophils are significantly increased in peripheral blood and skin lesions, suggesting that the pathogenesis is closely related to type 2 inflammation. Up to now, a variety of targeted drugs have been developed for the treatment of type 2 inflammatory diseases. Here we review the general process of type 2 inflammation, its role in the pathogenesis of bullous pemphigoid and potential therapeutic targets and medications to provide new ideas for the development of more effective drugs with less side effects in the therapy of bullous pemphigoid.